Relationship between anxiety, self-esteem and internet addiction among emerging adults in Malaysia - Sin, Rodney Ming Keen; Tan, Wai Yee; Yuon, Jia Xin (2020)
Internet addiction has reached an alarming rate. However, it was unclear that the correlation between of anxiety, self-esteem and internet addiction among emerging adults in Malaysia. Therefore, current study aimed to investigate the relationship between anxiety, self-esteem and internet addiction. The gender difference in internet addiction was examined as well. Current study used quantitative and cross-sectional research design. A total of 391 Malaysian emerging adults were recruited by using purposive sampling method. Internet Addiction Test (IAT), Rosenberg Self-Esteem Scale (RSES) and Beck Anxiety Inventory (BAI) were used in the present study. The independent sample t-test indicated that there is no significant gender difference in the internet addiction. Besides, Pearson correlation test revealed that there was a medium, significant negative correlation between anxiety and self-esteem and the Multiple regression analysis found that anxiety and self-esteem significantly predicted internet addiction. Current study highlighted the importance of considering the level of anxiety and self-esteem when addressing internet addiction. Hence, it has a vital implication for the targeted samples, educationalists, parents and also the legal authorities. Future study should use longitudinal study, develop bilingual survey and include validity scale to enhance the generalizability of the results.